2012
DOI: 10.1093/brain/aws182
|View full text |Cite
|
Sign up to set email alerts
|

Theta burst stimulation reduces disability during the activities of daily living in spatial neglect

Abstract: Left-sided spatial neglect is a common neurological syndrome following right-hemispheric stroke. The presence of spatial neglect is a powerful predictor of poor rehabilitation outcome. In one influential account of spatial neglect, interhemispheric inhibition is impaired and leads to a pathological hyperactivity in the contralesional hemisphere, resulting in a biased attentional allocation towards the right hemifield. Inhibitory transcranial magnetic stimulation can reduce the hyperactivity of the contralesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
171
0
21

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(196 citation statements)
references
References 84 publications
(106 reference statements)
2
171
0
21
Order By: Relevance
“…Our observation of a reduction in visuospatial neglect after cTBS over the unaffected PPC is in line with other noninvasive brain stimulation studies, which used singlepulse TMS and paired TMS as a 'virtual lesion' technique, 23,24 low-frequency ( 1 Hz) repetitive TMS, 17,24,25 cathodal transcranial direct current stimulation 26 or continuous TBS. 10,12 Koch et al 10 applied left PPC TBS in two sessions per day with an interval of 15 min every day for 2 weeks (10 days), which reduced hemispatial neglect for up to 2 weeks after treatment: behavioural inattention test scores improved by 16.3% at There were no significant differences between the treatment groups (post hoc tests: least significant difference or Student-Newman-Keuls). BG, basal ganglia; MCA, middle cerebral artery; R, right.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observation of a reduction in visuospatial neglect after cTBS over the unaffected PPC is in line with other noninvasive brain stimulation studies, which used singlepulse TMS and paired TMS as a 'virtual lesion' technique, 23,24 low-frequency ( 1 Hz) repetitive TMS, 17,24,25 cathodal transcranial direct current stimulation 26 or continuous TBS. 10,12 Koch et al 10 applied left PPC TBS in two sessions per day with an interval of 15 min every day for 2 weeks (10 days), which reduced hemispatial neglect for up to 2 weeks after treatment: behavioural inattention test scores improved by 16.3% at There were no significant differences between the treatment groups (post hoc tests: least significant difference or Student-Newman-Keuls). BG, basal ganglia; MCA, middle cerebral artery; R, right.…”
Section: Discussionmentioning
confidence: 99%
“…10, Another study showed a 37% improvement in the everyday behaviour of patients with visuospatial neglect for !3 weeks, after two consecutive days of continuous theta-burst stimulation. 12 Here, we used a modified version of a cTBS protocol that is known to be effective in inducing long-term depression and longlasting changes in the excitability of the stimulated cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the primary goal of the present study is to identify a therapy that will provide a greater likelihood of lasting successful results than has been achieved with ketamine or TMS along, while hopefully reducing the undesirable adverse effects of the conventional pharmacopoeia (Cazzoli et al, 2012;Gersner et al, 2011;Wang et al, 2011). …”
Section: Options For Treatment Resistant Depressionmentioning
confidence: 99%
“…Scores on the BIT improved by 16.3% immediately after TBS application and by 22.6% at 1 month follow-up. In a double-blind, shamcontrolled experiment, Cazzoli et al (2012) applied four TBS trains to the left posterior parietal cortex of 16 neglect patients over two consecutive days. This resulted in a 37% improvement in the spontaneous everyday neglect behavior of the patients as measured by the Catherine Bergego Scale.…”
Section: Non-invasive Brain Stimulationmentioning
confidence: 99%
“…In the present review we will describe the studies characterizing four of these approaches that have emerged since approximately a decade: prism adaptation (PA), virtual reality (VR) training, noninvasive brain stimulation (NIBS), and pharmacological therapies. Table S1 in Supplementary Material gives an overview of these studies (McIntosh et al, 2002, Angeli et al, 2004, Dijkerman et al, 2004, Jacquin-Courtois et al, 2008, Nijboer et al, 2011, Bauer et al, 2012, Luauté et al, 2012.…”
Section: Introductionmentioning
confidence: 99%